PENGARUH SUPLEMENTASI ASAM AMINO METIONIN DAN LYSIN PADA DOMBA YANG DIBERI PAKAN KARBOHIDRAT NON STRUKTURAL TERHADAP PERSENTASE KARKAS, DAGING DAN LUAS URAT DAGING MATA RUSUK - Abdusysyakur, Arif; Suryapratama, Wardhana; Setyaningrum, Agustinah (ANGON: Journal of Animal Science and Technology, 2022)
Background. The research aims to determine and examine the effect of adding the amino acid methionine and lysine to sheep fed wirh non-structural carbohydrates. Materials and Methods. The research material consisted of 18 male local sheep (thin tailed sheep) aged about 7-8 months. The treatments tested were R1 = ammoniated rice straw + concentrate (rice bran + coconut cake), R2 = R1 + amino acid methionine + lysine, R3 = ammoniated rice straw + concentrate (corn flour + soybean meal). The research method used is experimental in vivo, with a Randomized Complete Block Design (RCBD). The data generated during the study were analyzed using analysis of variance. Results. The results of the analysis of variance showed that the treatment had a significant effect (P<0.05) on the percentage of carcass, and the area of ??the rib eye tendon. The average value of the percentage of sheep carcasses in treatment R1, R2, R3, respectively, was 35,85%; 37,37%; 44,12%. In the percentage of meat, the average value of the percentage of lamb meat is 61,89%; 63,20%; 59,12%. In the percentage of fat, the average value of the percentage of lamb fat is 8,93%; 7,76%; 15,01%. And for the area of ??the rib eye area, the average value is 14,79 cm2, 15.88 cm2, 20,67 cm2. Conclusion. The addition of methionine and lysine amino acid supplementation can increase the percentage of carcass, meat and rib eye area.